2011
DOI: 10.3892/ol.2011.479
|View full text |Cite
|
Sign up to set email alerts
|

Association of CFTR gene polymorphisms with papillary thyroid cancer

Abstract: Abstract. The incidence of thyroid cancer has been on the increase in a number of countries, and certain genetic factors associated with the increased incidence of the papillary thyroid cancer (PTC) have been identified. However, little is known about the effect of mutations of the cystic fibrosis transmembrane conductance regulator (CFTR) gene, expressed in the thyroid. We hypothesized and investigated that CFTR single nucleotide polymorphisms (SNPs) may be associated with the risk and/or progression of PTC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Cystic fibrosis is also correlated with an increased risk of thyroid cancer [ 29 ]. Oh et al [ 30 ] reported that in PTC, two SNPs (rs4148682, promoter; rs213950, p.V470M) in CFTR have prognostic significance and may be associated with clinical features such as multifocality, cancer location, and cervical LN metastasis. In the TCGA database, the missense L702I mutation in CFTR was detected in a multifocal PTC (3.2 cm in the great dimension) along with N0 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis is also correlated with an increased risk of thyroid cancer [ 29 ]. Oh et al [ 30 ] reported that in PTC, two SNPs (rs4148682, promoter; rs213950, p.V470M) in CFTR have prognostic significance and may be associated with clinical features such as multifocality, cancer location, and cervical LN metastasis. In the TCGA database, the missense L702I mutation in CFTR was detected in a multifocal PTC (3.2 cm in the great dimension) along with N0 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…CFTR , a cAMP-activated chloride channel widely distributed in the epithelial cells of various tissues (28), plays an important role in maintaining cell homeostasis and is associated with metabolism (29). Mutations in CFTR are responsible for regulation of epithelial ion and water transport and fluid homeostasis, which affects the epithelial tissue of various organ systems, including the urogenital, respiratory and gastrointestinal systems (30). In addition, CFTR mutation increases the risk of various types of cancer, including lung, breast and colon cancer (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although rare, cases of thyroid tumors, melanomas, ovarian cancers, and brain tumors have been reported [17,62,90,96].…”
Section: Other Emerging Cancersmentioning
confidence: 99%